Elevated Plasma Level of 8-Hydroxy-2′-deoxyguanosine Is Associated with Primary Open-Angle Glaucoma - Altaf A. Kondkar; Taif A. Azad; Tahira Sultan; Essam A. Osman; Faisal A. Almobarak; Saleh A. Al-Obeidan (Journal of Ophthalmology)
Purpose. To determine the association between plasma 8-hydroxy-2′-deoxyguanosine (8-OHdG) levels, a marker for oxidative DNA damage, and patients with primary open-angle glaucoma (POAG) or its clinical phenotypes. Furthermore, we also examined the utility of plasma 8-OHdG as a potential biomarker in POAG. Materials and Methods. In a retrospective case-control study, plasma samples were obtained from 50 POAG cases and 45 glaucoma-free controls matched for age, sex, and ethnicity. 8-OHdG levels were measured in duplicate using an enzyme-linked immunosorbent assay (ELISA) on an automated ELISA analyzer. Results. There was no significant difference in age, sex, and systemic disease distribution between POAG cases and controls. Both mean and median 8-OHdG levels were significantly elevated in POAG cases and male subjects. The area under the receiver operating characteristic (ROC) curve value for plasma 8-OHdG was 0.653 (95% confidence interval = 0.54–0.76, p=0.010). The cutoff values based on quartile distribution and ROC curve analysis showed that elevated plasma 8-OHdG significantly increased the risk of POAG by more than 4-folds. Plasma 8-OHdG had a sensitivity of 78% and specificity of 53%. In logistic regression analysis, 8-OHdG showed a significant effect on POAG outcome (p=0.016) independent of age, sex, smoking, and systemic diseases. However, no significant correlation was observed between 8-OHdG and specific clinical markers of glaucoma such as intraocular pressure (p=0.699), cup/disc ratio (p=0.213), and the number of antiglaucoma medications (p=0.603). Conclusion. The study shows that there is a significant association between elevated plasma 8-OHdG and POAG, supporting the role of systemic oxidative stress-induced DNA damage in POAG pathogenesis. However, with a high rate of false-positivity, plasma 8-OHdG may lack the ability to serve as a potential biomarker in POAG. Further studies in a much larger cohort are needed to confirm these findings.